2003
DOI: 10.1211/0022357021837
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine-induced vasodilator responses in the hindquarters of the anaesthetized rat, involve β2-adrenoceptors

Abstract: These studies were conducted to examine the role of the vasoactive mediators nitric oxide (NO) and adrenaline (epinephrine) in the serotonin (5-hydroxytryptamine; 5-HT)-induced vasodilator response in the hindquarter vascular bed of anaesthetized rats. Intra-arterial administration of doses of 5-HT in the range 0.12-25 ng kg(-1) produced a dose-independent vasodilator effect in the hindquarters. The selective 5-HT(1D/1B) receptor agonist, L-694,247 at intra-arterial doses of 0.0012-1000 ng kg(-1), as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…3). This compound did not affect the mean blood pressure of the ani- mals but, as has been previously reported by us [17], it did inhibit the vasodilator effect of adrenaline (results not shown).…”
Section: Effect Of Ici 118551 On the Vasodilator Action Of M-cppsupporting
confidence: 84%
See 1 more Smart Citation
“…3). This compound did not affect the mean blood pressure of the ani- mals but, as has been previously reported by us [17], it did inhibit the vasodilator effect of adrenaline (results not shown).…”
Section: Effect Of Ici 118551 On the Vasodilator Action Of M-cppsupporting
confidence: 84%
“…results]. Accordingly, in the present work we studied the 5-HT receptors responsible for these actions and whether the local release of NA, as shown by us previously for selective 5-HT and 5-HT 1D agonists [17], contributes to the vasodilator action of m-CPP in the hindquarters or even if this vasodilator activity is not mediated by 5-HT receptor activation.…”
Section: Introductionmentioning
confidence: 63%
“…It has been suggested that local 5-HT 1B/1D activation in the sympathetic nervous system stimulates the release of adrenaline, which then can cause relaxation of vascular smooth muscle mediated by β 2 -adrenoceptor stimulation. 27) Additionally, chronic infusion of 5-HT produced a persistent fall in blood pressure in both deoxycorticosterone acetate (DOCA)-salt hypertensive rats and sham normotensive rats, which was contrary to expectations. 28) It has been suggested that 5-HT 1B (also 5-HT 2B and 5-HT 7 ) receptors may be involved in the dilation of peripheral arteries.…”
Section: Subtypes Of G Protein-coupled 5-ht Re-ceptors Involved In Lomentioning
confidence: 83%
“…25) Intra-arterial infusion of 5-HT or the selective 5-HT 1B/1D receptor agonist L-694247 was reported to produce vasodilation in the hindquarters of anaesthetized rats. 27) These effects may be explained by endotheliumdependent vasodilation. However, the NO synthase inhibitor N(G)-nitro-L-arginine (L-NAME) did not block while the selective β 2 -adrenoceptor antagonist ICI 118551 and bilateral adrenalectomy did block the vasodilation induced by the 5-HT infusion.…”
Section: Subtypes Of G Protein-coupled 5-ht Re-ceptors Involved In Lomentioning
confidence: 99%
“…We share here but a few examples. Calama et al (2003Calama et al ( , 2005 raise the interesting possibility that ␤ 2 adrenergic receptors are the effectors of 5-HTinduced vasodilation in the rat hindquarters, connecting 5-HT to the adrenal medulla (epinephrine release? ), because 5-HT itself does not have appreciable affinity for ␤-adrenergic receptors.…”
Section: -Hydroxytryptamine Synthesis and Handlingmentioning
confidence: 99%